GPS controlled autonomous walking robot - Bukhari, Ilias; R. Nagarajan; Sazali, Yaacob; Sundaraj, Kenneth (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 15th - 16th September 2006 at Pulau Langkawi, Malaysia.